Bronchoalveolar lavage immunodiagnosis for tuberculosis suspects in Europe and Africa - Lange, Christoph; Bossink, Aik; Eberhardt, Ralf; Goletti, Delia; Jafari, Claudia; Latorre, Irene; Kirsten, Detlef; Losi, Monica; Migliori, Giovanni B.; Sotgiu, Giovanni (Thorax, 2010)
We read with interest the article by Dheda et al 1 who followed our approach for a rapid diagnosis of smear-negative tuberculosis by bronchoalveolar lavage (BAL) enzyme-linked immunospot (ELISpot)2 in a country of high tuberculosis incidence, including individuals with HIV-1 infection. - - The authors report a sensitivity of 88.9% and specificity of 94.7% of the BAL ELISpot (T-SPOT.TB test) for the diagnosis of tuberculosis in suspects with scarce or negative acid-fast bacilli (AFB) sputum smears. This observation is important, as it confirms the findings of other …
Gesehen am 09.03.2023